El aprendizaje mediante las nuevas tecnologías de la comunicación y la información - Navarro Guzmán, José I. (Universidad Católica de Colombia. Facultad de Psicología, 2019)
New Computer Information-Communication Technology and Learning. Educational resources are considered as instructional tools daily used in classroom in order to improve the teaching efficiency. Because there is several teaching and learning technological tools, we just consider some rising computer and communication technologies. The purpose of this article is to analyze how important these new instructional tools are optimizing the learning teaching procedures for. On this way, we expose some procedures that support the teaching al learning process, like intelligent tutoring systems, computer assisted teaching, computer simulation, and artificial intelligent. In addition, some psychological process involved on the new technologies learning are also considered, particularly the organization, storage and retrieval knowledge.